Unlocking The Vague Meaning Al Qur’an of Surah Al Waqiah - Afif Kholisun Nashoih; Diki Iqbaluddin (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
ABSTRACT The Qur'an is the clear word of Allah that was sent down to the Prophet of the last days, Muhammad SAW. There is no single being that can match him because the Qur'an is at the highest level of fluency. And uslub iltifat is one of the topics of balaghah which can show the beauty of the sentences contained in the Al-Qur'an. Therefore, this study aims to determine the uslub iltifat and its balaghah values, then practice it in the waqiah letter. Uslub iltifat is one of the most important Arabic knowledge. Almost every letter of the Al-Qur'an is inseparable from the uslub iltifat In writing this thesis, the researcher uses the library method and refers to various sources, such as the Balaghah books related to research which are also the main sources of this research. Researchers also refer to the commentary books to find out the verses that contain the iltifat and their benefits. Researchers found that there was Iltifat in the letter al waqiah, among others, in terms of Iltifat in the form (ash-shigot) Numbers (al-adad) Pronouns (ad-dhomir)In the form (al-adawat)